Introduction and Application of Basic Accounting Principles and the Accounting Cycle at SMA Tarsisius 1 Jakarta - Erica Goh; Sriwati Sriwati (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2025)
Accounting training conducted at SMA Tarsisius 1 Jakarta aimed to enhance students' understanding of basic accounting and accounting cycle essential in the business world. The background of this initiative focused on the challenges students face in grasping complex accounting materials. The method employed was Team Assisted Individualization (TAI), where the lecturer presented theoretical accounting concepts at the beginning of each session, followed by guided practice where students worked in small groups with the support of the lecturer's assistants, along with quizzes to assess students' understanding. There are also survey results that indicate students can engage effectively in the learning process and reflect a significant improvement in their comprehension of accounting material. The conclusion drawn from this activity demonstrates that the training successfully met its objectives, enabling students to apply accounting concepts practically and relevantly. The students demonstrated significant improvement in tasks such as journaling transactions, posting transactions to the ledger, and also preparing trial balances, all of these are essential skills for them to tackle challenges in the field of accounting in the future.